The Effects of Adolescent Therapeutic Group Therapy and Cognitive Therapy on Emotional Mental Disorders of Adolescents - Anisa Yulvi Azni; Budi Anna Keliat; Ice Yulia Wardani (Jurnal Penelitian Pendidikan IPA, 2024)
The COVID-19 pandemic has changed adolescents’ lives, especially their daily activities. Therefore, they have to adapt to virtual school. This study aims to determine the effects of therapeutic group therapy and cognitive therapy in preventing emotional mental disorders of adolescents who have virtual schools during the COVID-19 pandemic. This study employed a quasi-experimental pre-post test design with the control group. The research sample was selected using purposive sampling and random sampling techniques; the sample size was 60 respondents divided into two groups. Intervention group 1 consisted of 30 people receiving therapeutic group therapy and cognitive therapy. Meanwhile, intervention group 2 consisted of 30 people receiving therapeutic group therapy without cognitive therapy. The univariate analysis employed the frequency distribution and central tendency. Meanwhile, the bivariate analysis employed a repeated ANOVA test for normally distributed data and the Friedman test for not normally distributed data. The results show that the combination of therapeutic group therapy and cognitive therapy has a significant effect on preventing emotional mental disorders in adolescents. This combination therapy is recommended to apply to prevent emotional mental disorders in adolescents who have virtual schools during the COVID-19 pandemic.